Apoptosis induction in leukemic cells by L-asparaginase preparation from Bacillus indicus: bench-scale production, purification and therapeutic application - Sharma D.; Mishra A. (My University, 2025)
With the emergence of multiple side effects on the usage of commercial L-asparaginase formulations, keen interest is provoked to investigate new sources of L-asparaginases that possess antileukemic properties with minimal side effects. The present study reports the cost-effective bench-scale production, homogeneity purification and apoptosis induction potential of a new L-asparaginase preparation from Bacillus indicus against human leukemia cells. The enzyme is highly specific toward the natural substrate L-asparagine. The study initiated with the enzyme production using cost-effective substrates in which a 3.28-fold enhancement of enzyme activity was achieved in comparison with an unoptimized medium using the central composite experimental design approach. The scale-up of the process in a 3.7-L batch bioreactor resulted in 16.42 ± 0.17 IU/mL of L-asparaginase activity in 24 h. The crude extracellular enzyme was purified to homogeneity using anion exchange chromatography followed by gel filtration chromatography. A single band of approximately 35 kDa molecular weight was obtained on SDS-PAGE, while native PAGE analysis confirmed it to be a tetramer of four identical subunits. The circular dichroism spectroscopic study revealed the α + β mixed type of secondary structure with 38.7% α-helices and 27.4% β pleated sheets. The antitumor toxicity exhibited on the MOLT-4 leukemia cells by the new L-asparaginase was revealed using the MTT assay and acridine orange/propidium iodide dual staining for live/dead cells. The flow cytometry analysis established the potential of the purified L-asparaginase to induce the apoptotic cell death mechanism in MOLT-4 leukemia cells. Conclusively, the L-asparaginase of Bacillus indicus is a highly promising candidate that can be introduced as a new enzyme therapeutic against various leukemia disorders. © 2022, King Abdulaziz City for Science and Technology.